2011
DOI: 10.1021/ic102449m
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Ph3Sb═S with Copper(I) Complexes Supported by N-Donor Ligands: Formation of Stable Adducts and S-Transfer Reactivity

Abstract: In the exploration of sulfur-delivery reagents useful for synthesizing models of the tetracoppersulfide cluster of nitrous oxide reductase, reactions of Ph 3 Sb=S with Cu(I) complexes of N,N,N', and 1,4,7-trialkyltriazacyclononanes (R 3 tacn; R = Me, Et, iPr) were studied. Treatment of [(R 3 tacn)Cu(NCCH 3 )]SbF 6 (R = Me, Et, or iPr) with one equivalent of S=SbPh 3 in CH 2 Cl 2 yielded adducts [(R 3 tacn)Cu(S=SbPh 3 )]SbF 6 (1-3), which were fully characterized, including by X-ray crystallography. The adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…18 Because 1 is extremely air sensitive, sample manipulation and loading into the XAS cells were performed in an inert atmosphere glove box. Samples were prepared for both solution (5 mM in CH 2 Cl 2 ) and polycrystalline Cu K-edge XAS measurements.…”
Section: Methodsmentioning
confidence: 99%
“…18 Because 1 is extremely air sensitive, sample manipulation and loading into the XAS cells were performed in an inert atmosphere glove box. Samples were prepared for both solution (5 mM in CH 2 Cl 2 ) and polycrystalline Cu K-edge XAS measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The Sb-S bond length of Et 3 SbS (2.381(7) Å), which is in between the calculated values for a Sb-S single bond (∑ cov (Sb,S) = 2.43 Å) [59] and a Sb=S double-bond (∑ cov (Sb,S) = 2.27 Å), [117] is significantly longer than that observed in Ph 3 Sb=S (2.244(1) Å). [30,31] Moreover, (Me 3 SbS) 2 Me 2 SnCl 2 (2.230(3 Å) [110] as well as three recently structurally characterized copper complexes of Ph 3 SbS (2.2735(9), 2.2812(7), 2.2832(7) Å) [111] show significantly shorter Sb-S bonds.…”
Section: Methodsmentioning
confidence: 89%
“…[30,31,32] In addition, transition metal and main group metal compounds of R 3 SbS were reported. [110,111] In contrast, solid state structures of selenostiboranes R 3 SbSe remained unknown, except for a single report, that describes their capability to serve as ligand in coordination chemistry. [112] Ph 3 SbS (2.244(1) Å) exhibits a short Sb-S bond, [113] which was described by Pebler as partial double bond due to dπ-pπ interaction.…”
Section: R 3 Sbe (E = S Se Te)mentioning
confidence: 99%
“…The sulfur transfer reagent, [SQSbPh 3 ], was reacted with copper(I) complexes in an attempt to synthesize model compounds for this enzyme. 61 It was found that initially formed adducts underwent slow decay in solution to form dinuclear dications containing the (m-Z 2 : Z 2 -S 2 ) ligand. Nitrosobenzene, PhNO, is an isoelectronic analogue of singlet oxygen used as a probe in copper(I) models of mononuclear monooxygenase enzymes.…”
Section: Bio-inspired Studiesmentioning
confidence: 99%